Філософсько-правове розуміння поведінки людини в доктринах природного та позитивного права - Омельчук, Олег Миколайович; Омельчук, Олег Николаевич; Omel'chuk, Oleg (My University, 2012)
The article is about the aspects of the human behavior in the philosophy of law, when the ideas of natural law had a revolutionary role in defending of possibilities of human, and also forming legally obligatory rules of conduct. Freedom was proclaimed as an inalienable right. In the philosophical ideas of natural law persons was examined as an owner of the life, which independently determines the conduct on the basis of good sense.
Омельчук О. М. Філософсько-правове розуміння поведінки людини в доктринах природного та позитивного права / О. М. Омельчук // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 216-224.
Keywords: поведінка людини; свобода; природне право; позитивне право; права людини; поведение человека; естественное право; позитивное право; права человека; human behavior; freedom; natural law; human rights